Aging of preleukemic thymocytes drives CpG island hypermethylation in T-cell acute lymphoblastic leukemia. - Roels, Juliette; Thénoz, Morgan; Szarzyńska, Bronisława; Landfors, Mattias; De Coninck, Stien; Demoen, Lisa; Provez, Lien; Kuchmiy, Anna; Strubbe, Steven; Reunes, Lindy; Pieters, Tim; Matthijssens, Filip; et al. (2020)
Cancer cells display DNA hypermethylation at specific CpG islands in comparison to their normal healthy counterparts, but the mechanism that drives this so-called CpG island methylator phenotype (CIMP) remains poorly understood. Here, we show that CpG island methylation in human T-cell acute lymphoblastic leukemia (T-ALL) mainly occurs at promoters of Polycomb Repressor Complex 2 (PRC2) target genes that are not expressed in normal or malignant T-cells and which display a reciprocal association with H3K27me3 binding. In addition, we revealed that this aberrant methylation profile reflects the epigenetic history of T-ALL and is established already in pre-leukemic, self-renewing thymocytes that precede T-ALL development. Finally, we unexpectedly uncover that this age-related CpG island hypermethylation signature in T-ALL is completely resistant to the FDA-approved hypomethylating agent Decitabine. Altogether, we here provide conceptual evidence for the involvement of a pre-leukemic phase characterized by self-renewing thymocytes in the pathogenesis of human T-ALL.